Prevalence of cardiovascular risk factors among executive and nonexecutive workers in an urban public sector office setting: A cross-sectional epidemiological study from Eastern India - Achintya Bhattacharya; Soumya Patra; Suvro Banerjee (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study is to determine the prevalence of cardiovascular risk factors among executive and nonexecutive workers in an urban public sector office setting. Methods: A prospective, cross-sectional survey of employees in a public sector office in Eastern India was done using a structured questionnaire to collect data on demographic and lifestyle details and health conditions. Clinical examination, anthropometric measurements, blood sugar, and lipid levels were measured. The employees were divided as executives and nonexecutives based on whether they held gazetted or nongazetted posts. Results: A total of 502 participants were surveyed - 140 executives and 362 nonexecutives; majority were male (88.23%). The executive group had a significantly greater number of participants with older age, hypertension (57.9% vs. 39%), and overweight (40% vs. 30.6%) than the nonexecutive group. Significantly, more nonexecutives had a physically active lifestyle and relatively less presence of conventional cardiovascular risk factors such as tobacco use, hypertension, diabetes, hypercholesterolemia, and weight. The prevalence of ≥3 cardiovascular risk factors was significantly high in executives (27.9%) as compared to nonexecutives (14.1%). Conclusion: A higher prevalence of mostly lifestyle-related modifiable cardiovascular risk factors was seen among the executives in an urban public sector office setting in Eastern India.